Clinical features of benign paroxysmal positional vertigo - Caldas,Mariana Azevedo (2009)
Benign paroxysmal positioning vertigo (BPPV) is considered as the most common vestibular disease. AIM: to evaluate the age, gender, type and site of the lesion, association with other vestibular diseases, progression, and recurrence in these patients. MATERIAL AND METHOD: A retrospective series study. Data from medical reports of BPPV patients examined in series during the past six years were analyzed. RESULTS: prevalences of BPPV were: at age 41-60 years (42.2 %); in females (62.8 %), wit nystagmus and positioning vertigo (81.3%); affecting the posterior canal (87%), unilateral (91.8 %), the right labyrinth (60.2%) - p<0.001). Due to canalithiasis (97.5%), idiopathic (74.8%), association with Menière's disease compared to other affections (55.4%); healing or recovery by means of the particle repositioning maneuver (77.9%); and possible recurrence (21.8% in a one-year follow-up period). CONCLUSION: BPPV is characterized by its prevalence at age 41 to 60 years, in females, with nystagmus and positioning vertigo, involving mostly the posterior canal of the right labyrinth, associated with canalithiasis or idiopathic, associated with Menière's disease compared to other affections, healing or recovery by means of particle repositioning maneuver, and possible recurrence.